Management of Critically Ill Pregnant Patients with COVID-19 Infection in a Rural State - Pagan, Megan E.; Ramseyer, Abigail M.; Whitcombe, Dayna D.; Doiron, Tucker E.; Magann, Everett F.; Sandlin, Adam T.; Hughes, Dawn S. (American Journal of Perinatology, 2021)
Objective There is limited data on the treatment of coronavirus disease 2019 (COVID-19) in pregnancy. Arkansas saw an increase in COVID-19 cases in June 2020. The first critically ill pregnant patient was admitted to our institution on May 21st, 2020. The objective of this study was to evaluate outcomes in critically ill pregnant women with COVID-19 at a single tertiary care center who received remdesivir and convalescent plasma (CCP).Study Design This is a retrospective observational review of critically ill pregnant women with COVID-19 who received remdesivir and CCP. This study was approved by the institutional review board (#261354).Results Seven pregnant patients with COVID-19 were admitted to the intensive care unit (ICU). All received remdesivir and CCP. Six received dexamethasone. The median ICU length of stay (LOS) was 8 days (range 3–17). Patient 1 had multi-organ failure requiring vasopressors, renal dialysis, and had an intrauterine fetal demise. Patients 4 and 6 required mechanical ventilation, were delivered for respiratory distress and were extubated at 2 and 1 days postpartum, respectively. The only common risk factor was obesity. There were no adverse events noted with remdesivir or CCP.Conclusion There is little data regarding the use of remdesivir or CCP for the treatment of COVID-19 in pregnant women. In our cohort, these were well tolerated with no adverse events. Previously reported median ICU LOS in critically ill pregnant women with COVID-19 was 8 days (range 4–15).1 Our study found a similar ICU LOS (8 days; range 3–17). Patient 1 did not receive remdesivir or CCP until transport to our facility on hospital day 3. Excluding patient 1, median ICU LOS was 6.5 days (range 3–9). Our institution's treatment of pregnant women with critical illness with remdesivir, CCP and dexamethasone combined with delivery in select cases has thus far had good outcomes.Key Points
Keywords: COVID-19; pregnancy; critical illness; remdesivir; convalescent plasma; dexamethasone; critical illness in pregnancy; coronavirus